2016
DOI: 10.1021/jacs.6b10836
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Asymmetric Epoxidation of Terminal Olefins Using Water as an Oxygen Source in the Presence of a Mononuclear Non-Heme Chiral Manganese Complex

Abstract: Photocatalytic enantioselective epoxidation of terminal olefins using a mononuclear non-heme chiral manganese catalyst, [(R,R-BQCN)Mn], and water as an oxygen source yields epoxides with relatively high enantioselectivities (e.g., up to 60% enantiomeric excess). A synthetic mononuclear non-heme chiral Mn(IV)-oxo complex, [(R,R-BQCN)Mn(O)], affords similar enantioselectivities in the epoxidation of terminal olefins under stoichiometric reaction conditions. Mechanistic details of each individual step of the phot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(38 citation statements)
references
References 42 publications
1
37
0
Order By: Relevance
“…To realize the above idea, we first synthesized the chiral Co complex DCo1 bearing tert-butyl groups starting from the commercially available chiral diamine 1a ( Figure 1b). [8] The sequential acylation/reduction operation afforded am ethylated diamine 2a;f urthermore,t he condensation of odiaminobenzene derivative 3a and ethyl chloroacetate provided chloromethyl-substitutedb enzimidazole 4a.T he subsequent alkylation of 2a with 4a under basic conditions gave an ew chiral N 4 ligand L1.F inally,c oordination of L1 with CoCl 2 ·(H 2 O) 6 in CH 3 CN completed the synthesis of designed chiral octahedral complex DCo1,which was confirmed by Xray crystallographic analysis. [9] As part of our ongoing research interest in visible-lightinduced asymmetric photochemical reaction, [10] we planned to examine the catalytic performance of the well-defined Co complex, DCo1,a sachiral Lewis acid catalyst in the benchmark photo-Giese reaction (conjugated addition to electron-deficient alkenes by photogenerated radicals).…”
mentioning
confidence: 99%
“…To realize the above idea, we first synthesized the chiral Co complex DCo1 bearing tert-butyl groups starting from the commercially available chiral diamine 1a ( Figure 1b). [8] The sequential acylation/reduction operation afforded am ethylated diamine 2a;f urthermore,t he condensation of odiaminobenzene derivative 3a and ethyl chloroacetate provided chloromethyl-substitutedb enzimidazole 4a.T he subsequent alkylation of 2a with 4a under basic conditions gave an ew chiral N 4 ligand L1.F inally,c oordination of L1 with CoCl 2 ·(H 2 O) 6 in CH 3 CN completed the synthesis of designed chiral octahedral complex DCo1,which was confirmed by Xray crystallographic analysis. [9] As part of our ongoing research interest in visible-lightinduced asymmetric photochemical reaction, [10] we planned to examine the catalytic performance of the well-defined Co complex, DCo1,a sachiral Lewis acid catalyst in the benchmark photo-Giese reaction (conjugated addition to electron-deficient alkenes by photogenerated radicals).…”
mentioning
confidence: 99%
“…[35][36][37][38][39][40][41][42][43][44][45][46][47] [Ru(bpy) 3 ] 3 + was used as ao neelectron oxidant to produce high-valent metal-oxo complexes, but it can be replaced by much milder oxidants such as [Co III (NH 3 ) 5 Cl] 2 + under photoirradiation. [48][49][50][51][52][53][54][55][56][57][58] Scheme2 shows the catalytic cycle of the photocatalytic oxygenation of watersoluble substrates (S) with [Co III (NH 3 ) 5 Cl] 2 + as an oxidanta nd [Ru(bpy) 3 ] 2 + as ap hotocatalyst and am anganese(III)-hydroxo porphyrin ([(Por)Mn(OH)]) as an oxygenation catalyst. [58] The photocatalytic oxygenation is started by photoinduced ET from [Ru(bpy) 3 ] 2 + *( where *d enotes the excited state) to [Co III (NH 3 ) 5 Cl] 2 + to produce [Ru(bpy) 3 ] 3 + ,w hich oxidizes [(Por)Mn(OH)] by ET to produce [(Por)Mn IV (O)].…”
Section: Productiono Fh Igh-valent Metal-oxo Complexes By Using H 2 Omentioning
confidence: 99%
“…[47] When the TMP ligand was replaced by TDCPP, [(TDCPP)Mn III ] + acts as a more reactive catalyst for the oxygenation of cyclohexene and styrene than [(TMP)Mn III (H 2 O) 2 ](PF 6 ), because of the smaller steric effect of the TDCPP ligand as comparedw ith that of TMP ligand and the high redox potential. [48][49][50][51][52][53][54][55][56][57][58] Scheme2 shows the catalytic cycle of the photocatalytic oxygenation of watersoluble substrates (S) with [Co III (NH 3 ) 5 Cl] 2 + as an oxidanta nd [Ru(bpy) 3 ] 2 + as ap hotocatalyst and am anganese(III)-hydroxo porphyrin ([(Por)Mn(OH)]) as an oxygenation catalyst. [47] Av ariety of high-valent metal-oxo complexes were produced by ET oxidation of metal complexes by one-electron oxidants, such as [Ru(bpy) 3 ] 3 + and cerium(IV) ammonium nitrate (CAN), with H 2 O, catalyzing oxygenation of substrates by using H 2 Oa sa no xygen source.…”
Section: Introductionmentioning
confidence: 99%
“…It has recently been reported that acetic acid plays a pivotal in the photocatalytic enantioselective epoxidation of terminal olefins in the presence of the mononuclear nonheme chiral manganese catalyst [( R , R ‐BQCN)Mn II (OTf) 2 ] [ 1 , BQCN= N , N′ ‐dimethyl‐ N , N′ ‐bis(8‐quinolyl)cyclohexanediamine], [Ru(bpy) 3 ] 2+ as the photocatalyst, [Co III (NH 3 ) 5 Cl] 2+ as the one‐electron oxidant, and water as the oxygen source (Scheme ) . Such photocatalytic oxidation reactions that employ [Ru(bpy) 3 ] 2+ as a photocatalyst, [Co III (NH 3 ) 5 Cl] 2+ as a one‐electron oxidant, water as an oxygen source, and various metal complexes without chiral ligands as catalysts have been previously reported .…”
Section: Asymmetric Photocatalytic Oxidationmentioning
confidence: 99%
“…It should be noted that virtually no epoxide was formed when the photocatalytic oxidation reactions were performed in the absence of 1 , [Ru II (bpy) 3 ] 2+ , [Co III (NH 3 ) 5 Cl] 2+ , or acetic acid, which indicates that all of these components are required for the formation of the epoxide . When acetic acid was replaced by other acids such as HOTf, HClO 4 , trifluoroacetic acid, or 2‐ethylhexanoic acid, no 2‐cyclohexyloxirane was produced . The replacement of acetic acid with acetate anions (e.g., CH 3 CO 2 Na) also failed to give the epoxide.…”
Section: Asymmetric Photocatalytic Oxidationmentioning
confidence: 99%